Обрядова функція народного вбрання на Волині другої половини XIX - початку XX ст. - Чайковська, Л. (Народна творчість та етнографія, 2007)
The importance of this research lies in looking into the problem of clothes related to ritual acts. It is aimed at finding out of sacral function of the national clothes in Volyn, throughout the period of the 19th and the beginning of the 20th century. Literary sources and exhibitions of museums in Western Ukraine are the bases of this work.